„Z dwóch stron czasu” – błyski „tamtych” zdarzeń w dyskursie literackim księdza Jerzego Szymika (PDF 460 KB) (Książnica Śląska, 2025)
The article discusses the subject of the silesian problems in the workof Rev. Jerzy Szymik from the perspective of post-memory concept,which was defined by Marianne Hirsch as an experience of peoplegrowing up in an environment dominated by a narration descending from the times before their birth. The experience was shared bythe poet, who had been raised among family stories of the timesbefore his was born. Traits of those memories are present in hispoetry, which has become a testify passing the memory heritage tonext generations.